ANALISYS OF THE EFFECT OF CORPORATE CREDIBILITY, ENDORSER IMAGE, AND AD APPEAL TOWARD BUYING INTEREST - Andi Tri Haryono (Jurnal Ekonomi dan Bisnis Kontemporer, 2015)
The purpose of this study was to develop a theoretical model of the research gap on endorserimage effects, adding intervening variables top of mind, for consumers to buy. The research object is selected in this study is a product of cellular card "AS". While the object of this research study were Consumer on Semarang City.Variables examined in this study include: The first variable is the corporate credibility, withindicators are the honesty of the corporate in providing the service or product information, corporate image, and corporate reputation. Then the second variable is the image endorser, with indicators are the modern image, humorous imagery, communicative imagery and charismatic image. Then the third variable is the Ad Appeal, the indicators are the story appeal, visual appeal, and the appeal of the word in the Ad. While an intervening variable in this study is Top of Mind with variable indicators are: the brand more memorable, the brand more quickly pronounced, the brand is often discussed, and the brand will be considered. While the dependent variable in this study is Buying Interests with indicator are looking for product information, go to the counter or outlet, and ask the seller. This study used Structural Equation Modeling (SEM) was run through the program AMOS version 18 as an analytical tool for the 231 respondents. Proposed research model is acceptable assuming the value of Standardized Residual Co-variance nothing more than ± 2.58 and the value of determinant of sample co-variance matrix = 1.124.Measurement of exogenous and endogenous constructs were tested using confirmatory factor analysis, and then test the feasibility of full models were analyzed using SEM, which generate value Chi-square = 131.366; probability = 0.114; GFI = 0.974; Cmin / DF = 1.059; TLI = 0998; CFI = 0999; and RMSEA = 0027. The entire index eligibility is in the expected range of value s. Results of the study's findings prove and conclude that the credibility of the corporate image endorser, and advertising appeal, the better able to increase top of mind then will influence consumers to buy.Keywords: Corporate Credibility, Image Endorser, Attraction Advertising, Top of Mind andCustomer Buying Interests.